Family centered psychosocial systemic approach in primary health care setting II: Social agendas and family centered interventions [Temel saǧlik hizmetlerinde aile merkezli sistemik psikososyal yaklaşim II: Toplumsal süreçler ve aile merkezli müdahaleler] - (:unkn) unknown (My University, 2007)
Social changes and attached medical referrals find their paths in the daily agendas of families and communities. Our paper will focus on the implementation of family based systemic psychosocial approach in community health car setting in Istanbul between the years of 2002-2004. Our model aims to reduce health depended social vulnerability and risks factors by integrating medical and psychosocial agendas of primary care referrals. Basic steps of systemic assessment and intervention were gathered under the topics of establishing a relation, connecting, contextualizing and supporting change. We hope that our experience provides an insight for future psychosocial models for primary health care.
Keywords: Community mental health; Family; Psychosocial approach; Systemic model